Heat efficiency of a solar trough receiver with a hot mirror compared to a selective coating - Cyulinyana, Marie; Ferrer, Phil (South African Journal of Science, 2011)
In this article, we present a solar trough system in which the receiver pipe is enclosed in a glass cover under vacuum. The dominant radiation losses from the receiver are reduced by the use of a ’hot mirror’ on the glass cover instead of a selective coating on the receiver pipe. We present the results for a general heat transfer model and compare the performance of a selective coating with that of a hot mirror, using simulations. We determined that a hot mirror is a viable alternative to a selective coating, and certainly allows higher temperatures of the working fluid. We recommend the use of a hybrid system, in which a selective coating is used in the part of the receiver pipe in the low temperature region, and a hot mirror is used in the high temperature region to reduce radiation losses.